Extracellular Tau and Its Potential Role in the Propagation of Tau Pathology - Yamada, Kaoru (Frontiers in Neuroscience, 2017)
The pathological aggregation of tau protein is a hallmark of a set of neurodegenerative diseases collectively referred to as tauopathies. Tau aggregates independently in each neuron, but this aggregation can also occur in a non-cell autonomous manner in which aggregated tau is transmitted from one cell to another. Such trans-cellular propagation is initiated by the uptake of extracellular tau, which then seeds soluble tau in the recipient cells to spread the tau pathology. Accumulating evidence has demonstrated that tau is not only present in the cytoplasm of neurons but also actively released into the extracellular space. This finding has led to the idea that extracellular tau could be a novel therapeutic target to halt the propagation of tau pathology. From this perspective, the present review article focuses on recent advances in understanding the mechanisms regulating the levels of extracellular tau and discusses the role of such mechanisms in the propagation of tau pathology.